MEDIA WAYANG DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Suhestiwi, Rini; Junita, Ika Elsa; Damayanti, Novita (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This research explores the use of wayang media as a medium for learning the history of Islamic culture. Wayang, which has strong cultural roots in Indonesia, can be an effective medium for conveying Islamic historical values ​​to students. Through a literature review, we examine how wayang can bring Islamic historical narratives to life, enrich learning experiences, and increase students' understanding of the material being taught. The research results show that the use of wayang in learning the history of Islamic culture not only increases students' interest and participation, but also helps them internalize Islamic cultural values ​​more deeply.